Improvement of thyroid function in POEMS syndrome after combination therapy of lenalidomide and dexamethasone. Issue 2 (28th January 2019) - Yang, Hongbo; Zhao, Hao; Huang, Xufei; Cao, Xinxin; Zhou, Daobin; Li, Jian
Abstract: Hypothyroidism is the most common endocrine disorder in POEMS syndrome. In this single-center prospective study, 36 patients with newly diagnosed POEMS syndrome were treated with lenalidomide (10 mg daily for 21 days) and dexamethasone (40mg once per week) for 12 cycles. Hypothyroidism was demonstrated in 58.5% (24/41) at baseline, including 25% (6/24) of clinical hypothyroidism and 75% (18/24) of subclinical hypothyroidism. After 12-month treatment, the percentages of clinical hypothyroidism and subclinical hypothyroidism had decreased 11.8% and 27.2%, respectively. Percentage of euthyroidism had increased from 41.5% to 80.5%. There was a strong relation between VEGF response and thyroid function improvement ( p = .028). Patients with clinical hypothyroidism at baseline had an inferior 1-year OS (50% vs. 100%, p < .043) than euthyroidism and subclinical hypothyroidism groups. Clinical hypothyroidism was associated with decreased overall survival and this combination treatment was effective in improving thyroid function in POEMS syndrome.